2018
DOI: 10.1113/jp276432
|View full text |Cite
|
Sign up to set email alerts
|

A moderate oestradiol level enhances neutrophil number and activity in muscle after traumatic injury but strength recovery is accelerated

Abstract: Oestrogen has been shown to protect against skeletal muscle injury and a reduced inflammatory response has been suggested as a possible protective mechanism. There are, however, dissenting reports. Our objective was to conduct an unbiased, comprehensive study of the effect of oestradiol on the inflammatory response following muscle injury. Female C57BL6/J mice were ovariectomized and supplemented with and without oestradiol. Tibialis anterior muscles were freeze injured and studied primarily at 1-4 days post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…In an article in this issue of The Journal of Physiology , Le et al . () note that these previous studies have contradictory findings, in that oestrogen has been reported to either attenuate or augment post‐damage muscle inflammatory responses, and they suggest that differing levels of circulating oestrogen used in these studies might explain the discrepancies. Le et al .…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…In an article in this issue of The Journal of Physiology , Le et al . () note that these previous studies have contradictory findings, in that oestrogen has been reported to either attenuate or augment post‐damage muscle inflammatory responses, and they suggest that differing levels of circulating oestrogen used in these studies might explain the discrepancies. Le et al .…”
mentioning
confidence: 79%
“…Interestingly, Le et al . () also found a more rapid muscle force recovery in mice with ‘normal’ oestrogen levels than in the non‐supplemented mice with lower than ‘normal’ oestrogen levels. Hence, they suggested that augmented post‐damage muscle inflammation as induced by modest or normal oestrogen levels may result in enhanced stimulation of various signalling factors that upregulate the rate of muscle repair.…”
mentioning
confidence: 80%
See 3 more Smart Citations